COMPREHENSIVE PERFORMANCE ASSESSMENT OF HYBRID RENEWABLE ENERGY SYSTEMS FOR RESIDENTIAL BUILDING APPLICATIONS (Journal of Multidisciplinary Sciences and Innovations, 2025)
This study evaluates the performance of hybrid renewable energy systems (HRES) in residential buildings with respect to energy efficiency, environmental impact, and economic feasibility. The analysis highlights the effectiveness of integrated systems combining solar technologies, hydrogen storage, advanced thermal storage, and biomass-based solutions in reducing primary energy consumption and carbon emissions. The findings indicate that well-optimized HRES configurations significantly enhance operational reliability and support the development of near-zero energy buildings, demonstrating their critical role in sustainable residential energy systems.